PFAS in water environments: recent progress and challenges in monitoring, toxicity, treatment technologies, and post-treatment toxicity - Aya Alsadik; Olufemi Oluseun Akintunde; Hamid R. Habibi; Gopal Achari (Environmental Systems Research)
Abstract There is growing awareness of the environmental presence of per- and polyfluoroalkyl substances (PFAS) and their harmful effects on animals and humans. Recent studies have revealed changes in human embryonic stem cells and maternal biomarkers, underscoring the severity and unpredictable outcomes associated with long-term exposure to PFAS. Monitoring efforts continually identify additional PFAS compounds worldwide, but a standardized and unified approach is still lacking. Traditional treatment methods such as adsorption and membrane filtration have been effective in removing 80–95% of PFAS from wastewater. However, complete removal of short-chain PFAS remains limited to a few recently developed techniques. The inability of advanced treatment methods to eliminate emerging short-chain and ultrashort-chain PFAS suggests the need for more integrated approaches that target all PFAS classes. Additionally, a few studies have discussed the potential toxicity outcomes of these treatments at both laboratory and full-scale levels. While advanced oxidative processes (AOPs) are rapidly gaining attention for degrading 90–100% of PFAS in sewage, it remains challenging to fully break down PFAS into non-toxic, mineralized products such as CO2 and H2O due to the strong C-F bonds and the potential toxicity of by-products in post-treated wastewater. Standardized and reliable bioassays for assessing PFAS toxicity are still under development, and current predictive models linking molecular structure to human health effects are at an early stage. This review examines the emerging health and ecological risks associated with both legacy and novel PFAS, alongside recent advances and limitations in individual and combined treatment technologies for water and wastewater. Emphasis is placed on the potential toxicity of degradation products, highlighting the need for more integrated and comprehensive toxicity assessments to guide safer PFAS remediation strategies.